The encryption algorithm "FC" and analysis of its avalanche effect criterion - Nyssanbayeva С.Е.; Algazy К.Т.; Sakan Қ.С.; Khompysh, A.; Dyussenbayev Д.С. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2022)
The article is about the importance, features and scope of symmetric block ciphers used to ensure the confidentiality of data in the era of rapid development of modern computing technologies. In this paper, the structure of the symmetric block encryption algorithm CF, developed in the "Laboratory of Information Security" of the "Institute of Information and Computational Technologies", the round keys generating mechanism based on it’s secret key are described. A computer program of the created encryption algorithm was developed, on the basis of which the performance was studied and the bit scattering between the plaintext and the ciphertext (the property of the "avalanche effect" and "strong avalanche effect") was checked. In order to optimize the hardware implementation of the algorithm, the conversion of the S-block, which is considered as a nonlinear node, was obtained in 4x4 bit size.